Atypical polyneuropathy caused by varicella Zoster virus: Involvement of vestibulocochlear, glossopharyngeal and vagus nerves - Silva Ferreira, Mafalda (2019)
Varicella-zoster virus stays latent in our body after a primary infection. Herpes zoster appears after its reactivation. The most common presentation of this type of virus, in head and neck region, is the Ramsay Hunt syndrome (facial palsy, otic herpes and hearing loss). We report a case of a patient with an atypical and rare herpes-zoster manifestation which envolved concomitantly the VIII, IX and X cranial nerves, preserving the VII.